Integer programming and combinatorial optimization : 21st International Conference, IPCO 2020, London, UK, June 8-10, 2020, Proceedings /: 21st International Conference, IPCO 2020, London, UK, June 8-10, 2020, Proceedings. (2020) - Unknown
No abstract available